ANALISIS KESULITAN SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA MATERI PROGRAM LINIER BERDASARKAN GAYA BELAJAR SISWA - Trizulfianto Trizulfianto; Dewi Anggreini; Adi Waluyo (UNION: Jurnal Ilmiah Pendidikan Matematika, 2017)
The purpose of this research is (1) to know the difficulties experienced by students who have visual learning style in solving the problem (2) to know the difficulties experienced by students who have an auditory learning style in solving the problem (3) to know Difficulties experienced by students who have kinesthetic learning style in solving problems This research uses descriptive qualitative research methods. This study obtained data from questionnaire learning style, writing test math problems and interview results to students. Data analysis techniques by reducing data presents data and draw conclusions. The validity of the findings is checked using triangulation and peer examination. The results of this study are students experiencing 4 types of difficulty in solving problems based on learning style that is (1) difficulty in linguistic skill, (2) difficulties in perceptual skill, (3) difficulties in mathematic skill, (4) difficulty in atentic skill. For students with visual learning styles experiencing difficulties in mathematical skills and atential skills in solving problems, students with auditory learning styles have difficulty in linguistic skills, difficulties in perceptual and atential skills in solving problems, students with kinesthetic learning styles tend to have difficulty in linguistic skills And atent in solving problems.